MENINGKATKAN PEMAHAMAN PESERTA DIDIK DENGAN MENGGUNAKAN PAPAN POLASTE PADA MATERI PENGENALAN POLA BILANGAN DI KELAS I SD NEGERI 066050 MEDAN DENAI: Penelitian Tindakan Kelas - Dhea Nabila; Indra Maryanti; Duma R. Pasaribu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve students’ understanding of the topic of number pattern recognition by using a concrete media called the Polaste board in Grade 1 at SD Negeri 066050 Medan Denai. The method used was Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action, observation, and reflection. The results showed that the use of the Polaste board successfully enhanced students' understanding. In the pre-cycle stage, the average student score was 63.58 with a mastery level of 23.53%. After the first cycle, the average score increased to 71.05 with 58.82% achieving mastery. In the second cycle, the average score reached 85.58 with a mastery level of 70.59%. These improvements demonstrate that the Polaste board is an effective teaching tool for strengthening students’ conceptual understanding of number patterns in early grade mathematics education.